Meningkatkan Nilai OEE Mesin Cutting Pada Line 6 Finishing Dengan Metode RCA di PT. XYZ - Suwarno, Agus; Widya, Adi Rusdi (DPPM UNIVERSITAS PELITA BANGSA, 2021)
PT. XYZ is an automotive manufacturing company. Problems during the production process are very important to be analyzed. Analysis of these problems needs to be done, especially on the production machines used. With OEE analysis (overall equipment effectiveness) functions to see the overall condition which includes the level of availability, performance level, and quality level. Using a machine that is less efficient there are six factors which are called the six major disadvantages. From the results of the calculation of the OEE value on the cutting line 6 finishing machine, it is still below the standard word class manufacturing (WCM) with an average of 81.18%. The results of the calculation of the six major losses, the factors that influence the low value of OEE are damage losses (49.16%) and adjustment and adjustment (38.13%). To see the root of the problem as a whole, an analysis was carried out using the RCA (Root Cause Analysis) method and provided improvements with an average OEE result of 94.45%.